2010
DOI: 10.1063/1.3292210
|View full text |Cite
|
Sign up to set email alerts
|

Laser spectroscopy of gas confined in nanoporous materials

Abstract: We show that high-resolution laser spectroscopy can probe surface interactions of gas confined in nano-cavities of porous materials. We report on strong line broadening and unfamiliar lineshapes due to tight confinement, as well as signal enhancement due to multiple photon scattering. This new domain of laser spectroscopy constitute a challenge for the theory of collisions and spectroscopic lineshapes, and open for new ways of analyzing porous materials and processes taking place therein.Comment: 4 pages, 3 fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 39 publications
(60 reference statements)
4
27
0
Order By: Relevance
“…Accordingly, the turbid material between holes, is found to exhibit t ranging from 0.7 µm at 600 nm to 2.2 µm at 900 nm and low absorption (0.026 cm −1 at 660 nm down to 0.005 cm −1 at 900 nm). The small size of the nanopores makes scattering strongly wavelength-dependent, and the transport scattering coefficient µ s decays as ∼ λ −2.7 (in good agreement with previous reports on scattering of nanoporous ceramics [48,51]). Figure 5a shows the diffusivity spectra for the holey (bimodal) system and for the nanoporous reference, and compares it to MC and the proposed analytical model.…”
Section: Diffusion Equation In Spherical Shells (Derivation Given Insupporting
confidence: 70%
“…Accordingly, the turbid material between holes, is found to exhibit t ranging from 0.7 µm at 600 nm to 2.2 µm at 900 nm and low absorption (0.026 cm −1 at 660 nm down to 0.005 cm −1 at 900 nm). The small size of the nanopores makes scattering strongly wavelength-dependent, and the transport scattering coefficient µ s decays as ∼ λ −2.7 (in good agreement with previous reports on scattering of nanoporous ceramics [48,51]). Figure 5a shows the diffusivity spectra for the holey (bimodal) system and for the nanoporous reference, and compares it to MC and the proposed analytical model.…”
Section: Diffusion Equation In Spherical Shells (Derivation Given Insupporting
confidence: 70%
“…1 a mean free path of 60 nm for molecules in air at atmospheric pressure, a broadening is certainly expected [12]. The data presented in Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Under confinement, however, the molecules will collide with the walls and become perturbed, resulting in further broadening of the absorption lines. The geometry of the confinement will determine the wall-collision rate, and it has been experimentally shown that the broadening exhibits a pore-size dependence [12,13,18,19]. Prediction of the total collision broadening of absorption lines is, on the other hand, highly nontrivial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding of the interaction of light and turbid porous materials is of fundamental importance in many areas-from fundamental studies of photon localization in porous semiconductor materials [1,2] to analysis of chemistry, pore structure and optics of powders and pharmaceutical materials [3][4][5], porous ceramics [6][7][8], and porous silicon [9,10]. Throughout the years, massive efforts have been put into developing models for the macroscopic aspects of photon migration in turbid materials.…”
Section: And Stefan Andersson-engelsmentioning
confidence: 99%